Factors associated with nonsyndromic anotia and microtia, Texas, 1999–2014. Issue 1 (17th November 2022) - Schraw, Jeremy M.; Woodhouse, J. P.; Benjamin, Renata H.; Shumate, Charles J.; Nguyen, Joanne; Canfield, Mark A.; Agopian, A. J.; Lupo, Philip J.
Abstract: Background: Few risk factors have been identified for nonsyndromic anotia/microtia (A/M). Methods: We obtained data on cases and a reference population of all livebirths in Texas for 1999–2014 from the Texas Birth Defects Registry (TBDR) and Texas vital records. We estimated prevalence ratios (PRs) and 95% confidence intervals (CIs) for A/M (any, isolated, nonisolated, unilateral, and bilateral) using Poisson regression. We evaluated trends in prevalence rates using Joinpoint regression. Results: We identified 1, 322 cases, of whom 982 (74.3%) had isolated and 1, 175 (88.9%) had unilateral A/M. Prevalence was increased among males (PR: 1.3, 95% CI: 1.2–1.4), offspring of women with less than high school education (PR: 1.3, 95% CI: 1.1–1.5), diabetes (PR: 2.0, 95% CI: 1.6–2.4), or age 30–39 versus 20–29 years (PR: 1.2, 95% CI: 1.0–1.3). The prevalence was decreased among offspring of non‐Hispanic Black versus White women (PR: 0.6, 95% CI: 0.4–0.8) but increased among offspring of Hispanic women (PR: 2.9, 95% CI: 2.5–3.4) and non‐Hispanic women of other races (PR: 1.7, 95% CI: 1.3–2.3). We observed similar results among cases with isolated and unilateral A/M. Sex disparities were not evident for nonisolated or bilateral phenotypes, nor did birth prevalence differ between offspring of non‐Hispanic Black and non‐Hispanic White women. Maternal diabetes was more strongly associated with nonisolated (PR: 4.5, 95% CI: 3.2–6.4) and bilateral A/M (PR: 5.0, 95% CI: 3.3–7.7). Crude prevalence rates increased throughout the study period (annual percent change: 1.82). Conclusion: We identified differences in the prevalence of nonsyndromic A/M by maternal race/ethnicity, education, and age, which may be indicators of unidentified social/environmental risk factors.